Dampak Komunikasi dan Kepercayaan terhadap Performa Tim Manajemen Wakaf Air Minum di Pondok Pesantren Riyadlul Jannah Pacet Mojokerto - Joko Wiyono (FADZAT: Jurnal Ekonomi Syariah, 2021)
The achievement of organizational goals in Islam is strongly influenced by the performance of its leaders. Quality of Organizational Communication with the strength of a leadership position to create a strong influence on subordinates and colleagues is seen as an indicator of a good leader. The purpose of this study was to analyze the influence of communication simultaneously, partially and dominantly on the variables of communication and trust on team performance. The research method explains that the location of Waqf Drinking Water Management in Pondok Pesantren Riyadlul Jannah Pacet Mojokerto as a Government Institution, the type of research is explanatory research, namely research that aims to determine the relationship between the two variables Communication and Trust on Team Performance. The population of the study was the employees of Waqf Drinking Water Management at the Riyadlul Jannah Islamic Boarding School Pacet Mojokerto. The number of samples was 93 people, while the data analysis used multiple linear regression. The results showed that: 1) There was a simultaneous effect of communication and trust on team performance. 2) There is a partial effect of communication on team performance and there is a partial effect of trust on team performance. 3) communication has a more dominant effect on team performance than trust.